The value of 3D-speckle tracking longitudinal strain for the assessment of left ventricular function recovery in ischemic heart failure patients undergoing surgical remodeling:the RECOVERY-IN study. (25th November 2020) - Castelvecchio, S; Frigelli, M; Sturla, F; Citarella, M; Pappalardo, O.A; Milani, V; Guastafierro, F; Menicanti, L; Votta, E
Abstract: Background: Three-dimensional (3D) speckle-tracking echocardiography is largely employed to evaluate left ventricle (LV) morphology and function. Purpose: To investigate LV function before and after surgical ventricular reconstruction (SVR) through the analysis of global (GLS) and segmental (SLS) longitudinal strain, and the derived mechanical dispersion (MD). Methods: Twenty patients eligible for SVR, with previous LV remodelling and ischemic heart failure (HF), received 3D echocardiographic evaluation before SVR and at 6-months follow-up; 15 normal controls, matched by age and BSA, were enrolled. Standard off-line GLS analysis was performed with 4D LV-ANALYSIS©; advanced segmental analysis was accomplished automatically through in-house numerical post-processing. Results: Before SVR, GLS deteriorated compared to normal subjects (−6.7% vs. −19.6%, P<0.0001) as confirmed by SLS at each LV segment basal, mid and apical level (P<0.0001); MD was higher than in controls (P<0.001) and markedly increased from basal to apical LV segment. After SVR, GLS significantly improved from −6.7% to −11.3% (P<0.0001). Analysis of variance showed that SLS recovery was higher in the basal region (7.25%) than in both mid (4.06%, P=0.001) and apical (1.92%, P<0.0001) segments, respectively, with adjustment for baseline values. Conclusions: After SVR, LV longitudinal strain mostly improves in the basal segments, outlining the role of the remote myocardium in enhancing LV function through an extensive volume reduction; post-surgical MD reduction indicates a more homogeneous myocardial contraction. Funding Acknowledgement: Type of funding source: Private hospital(s). Main funding source(s): IRCCS Policlinico San Donato is a clinical research hospital partially funded by the Italian Ministry of Health.